Glycated albumin is a better indicator for glucose levels than glycated hemoglobin in patients with diabetes mellitus on insulin therapy - Pusparini, Pusparini; Meiyanti, Meiyanti; Merijanti, Lie T; Lesmana, Alvina (Universa Medicina, 2020)
BackgroundDiabetes mellitus (DM) is a metabolic disease with a large incidence in the world and constitutes a global health problem. By 2030 it is estimated that there will be around 439 million people suffering from DM. Diabetes mellitus is a metabolic disease caused by a lack or absence of the hormone insulin. In type 2 DM pharmacotherapy can be given one of which is insulin. To monitor therapy, random blood glucose, glycated hemoglobin (HbA1c) and glycated albumin (GA) levels can be examined. The objective of this study was to determine the relationship of glycated albumin and glycated hemoglobin (HbA1c) with random blood glucose in insulin-treated diabetics.MethodsA cross-sectional study was conducted involving 92 type 2 diabetic patients treated with insulin. The study used a questionnaire and blood samples. We measured the GA , HbA1C and random blood glucose levels. A multiple linear regression was used to analyze the data. ResultsMean HbA1c was 9.21 ± 2.15%, mean glycated albumin was 24.4 ± 8.65%, and mean blood glucose was 229.47 ± 98.7 mg/dL. Multiple linear regression tests showed that HbA1c (B= 5,544; â=0.121; p=0.420) and GA (B=5.899; â=0.517; p=0.001) was signigicantly corelated with random blood gucose, respectively, indicating that glycated albumin is significantly related to and has the greatest influence on glucose level.ConclusionGlycated albumin is correlated with and has greater influence on glucose level than does HbA1c. Glycated albumin could be a better marker for glycemic control than glycated hemoglobin in diabetic patients treated with insulin.